Identification of compounds against atherosclerosis induced by ox-LDL based on cell extraction/UPLC–MS/MS from mulberry twigs and their mechanistic analysis - Zhihui Jin; Wei Xiang; Xiaowen Shi; Fenglin Jiang; Yanan Jia; Yuansong Zhang; Lingshu Zeng; Xianzhi Huang; Li Xu (Chemical and Biological Technologies in Agriculture)
Abstract Background Mulberry twigs, a traditional Chinese medicinal and agricultural byproduct, contain bioactive compounds with anti-atherosclerotic potential. This study aims to identify and evaluate the effects of key compounds in mulberry twig extracts (MTEs) on oxidized low-density lipoprotein (ox-LDL)-induced human umbilical vein endothelial cells (HUVECs), with a focus on understanding how these compounds modulate oxidative stress and related signaling pathways. Methods Biospecific cell extraction and ultra-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) were employed to screen and identify these compounds. Protective effects were assessed by measuring cell viability, malondialdehyde (MDA), and superoxide dismutase (SOD) levels, along with detecting intracellular reactive oxygen species (ROS) using 2, 7-dichlorodihydrofluorescein diacetate (DCFH-DA) and dihydroethidine (DHE) probes. Real-time qPCR and Western blotting were used for mRNA and protein level analysis. Results Two novel active compounds, Kuwanon H and Morusin, and the known Kuwanon G, were identified. They significantly reduced MDA and ROS levels while increasing SOD activity in ox-LDL-treated HUVECs. Kuwanon H was particularly effective, enhancing nuclear factor erythroid 2-related factor 2 (Nrf-2) activity and upregulating its target genes Heme oxygenase-1 (HO-1) and NAD(P)H: quinone oxidoreductase 1 (NQO-1). Conclusion In conclusion, Kuwanon H, Morusin, and Kuwanon G effectively protected HUVECs from ox-LDL-induced oxidative injury, with Kuwanon H showing the strongest protective effects via the Nrf-2/HO-1 signaling pathway. These compounds hold potential in treating atherosclerosis and related oxidative stress diseases. Graphical Abstract